Quantification of the Relationship Between the Height – Diameter of (Pinus brutia Ten), Calabrian Pine Trees in Four Different Microsites in Duhok Governorate. Kurdistan Region, Iraq - Salih, Tariq K.; Abdulaziz, Hayfaa M. Saaed (Science Journal of University of Zakho, 2023)
A sample of 120 trees was purposely selected from four different microsites (Behere, Swaratoka, Zawita, and Semel), (30 trees from each microsite) in the Duhok governorate. 100 of which were used for model calibration and the rest were used for validation of the selected regression equation. This study consisted of two main parts. In the first part ,In the beginning, a scatter diagram was conducted for each microsite to detect the type of relationship between height and diameter at breast, which in turn will decrease the number of regression models that will be tested. Accordingly, 4 regression equations were developed for each of the four microsites separately. These models can be used to see how the ratio of height diameter in each of the studied sites is inter-correlated and which of them is the most appropriate for producing Calabrian pine trees. In the second part, all microsites were then treated as one sample for estimating the parameters of 25 regression models using Excel and Statographic packageThe developed regression models underwent a screening process in order to find the most appropriate one to be used for the prediction of the height of Calabrian pine grown in the four mentioned microsites in Duhok governorate. Many measures of precision among them coefficient of determination, Bias%, Mean absolute error, Ohtomo’s unbiased test, Furnival Index, and AIC criterion were used for testing the performance of the developed equations in the prediction of the height. At last, the equation was selected, as the best regression model. This equation shows that there is a linear relationship between and a curvilinear relationship between D and H. The study showed that the height–diameter ratio was highest in Swaratoka and was the most appropriate microsite among the rest, followed by Behere, then Zawita and Semel came in last place.